2006
DOI: 10.1080/02643290600576595
|View full text |Cite
|
Sign up to set email alerts
|

How do World-Class Cricket Batsmen Anticipate a Bowler's Intention?

Abstract: Four experiments are reported that examine the ability of cricket batsmen of different skill levels to pick up advance information to anticipate the type and length of balls bowled by swing and spin bowlers. The information available upon which to make the predictive judgements was manipulated through a combination of temporal occlusion of the display and selective occlusion or presentation of putative anticipatory cues. In addition to a capability to pick up advance information from the same cues used by inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
185
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 234 publications
(197 citation statements)
references
References 26 publications
12
185
0
Order By: Relevance
“…As predicted, the expert participants were significantly more accurate at anticipation on the temporal occlusion test compared to the novice participants. Findings support previous research showing that expert athletes are better than novice athletes at anticipating upcoming actions (Abernethy, Gill, Parks, & Packer, 2001;Dicks, Button, & Davids, 2010;Gabbett, Rubinoff, Thorburn, & Farrow, 2007;Muller, Abernethy, & Farrow, 2006;Savelsbergh et al, 2002;Williams et al, 2002), especially earlier in the execution of the action (Abernethy, 1990;Williams et al, 2002). The expert group have a significantly greater amount of domain specific experience, thus enabling them to combine the current environmental situation with those previous experiences to aid in response selection (Causer et al, 2012), whereas the novices do not.…”
Section: Discussionsupporting
confidence: 83%
“…As predicted, the expert participants were significantly more accurate at anticipation on the temporal occlusion test compared to the novice participants. Findings support previous research showing that expert athletes are better than novice athletes at anticipating upcoming actions (Abernethy, Gill, Parks, & Packer, 2001;Dicks, Button, & Davids, 2010;Gabbett, Rubinoff, Thorburn, & Farrow, 2007;Muller, Abernethy, & Farrow, 2006;Savelsbergh et al, 2002;Williams et al, 2002), especially earlier in the execution of the action (Abernethy, 1990;Williams et al, 2002). The expert group have a significantly greater amount of domain specific experience, thus enabling them to combine the current environmental situation with those previous experiences to aid in response selection (Causer et al, 2012), whereas the novices do not.…”
Section: Discussionsupporting
confidence: 83%
“…Research in cricket batting has demonstrated a relationship between skill level and anticipation, consistent with those seen in other sports (Müller, Abernethy, & Farrow, 2006). Current evidence from expertise research suggests that only skilled batters have an ability to utilize information from the prerelease actions of a bowler (Weissensteiner et al, in press).…”
Section: The Use Of Ball Projection Machinesmentioning
confidence: 68%
“…Specifically, they make use of the motion of the bowling arm, in relation to the bowling hand, primarily between the time of front foot impact and ball release 85 . Differences in information pickup are found between novices and skilled cricketers, but also between skilled and elite players 85 .…”
Section: Anticipatory Information Pick-up In Expert Performersmentioning
confidence: 99%